Optimal waiting period for frozen embryo transfer after hysteroscopic polypectomy: A propensity score matching analysis - Wang, Bijun; Meng, Nan; Zhang, Wenjuan; Kong, Pingping; Liu, Zhaozhao; Liu, Wenxia; Sun, Huaqing; Zhang, Wen; Ren, Chenchen; Guan, Yichun (Frontiers in Endocrinology, 2022)
Objective: To evaluate the optimal waiting period for frozen-thawed embryo transfer (FET) after hysteroscopic polypectomy (HSC-P). Design: Retrospective cohort. Setting: University-affiliated hospital. Patient(s): All patients included in this research underwent hysteroscopy before the first FET cycle after whole embryo freezing. A total of 206 patients had undergone HSC-P, and 3681 patients without endometrial polyps were defined as the controls. Intervention(s): HSC-P. Main outcome measure(s): The HSC-P group was divided into three subgroups based on the time interval between HSC-P and the start of an FET cycle. Subgroup 1 consisted of patients who underwent FET after their next menses, subgroup 2 after two menstrual cycles, and subgroup 3 after three or more menstrual cycles. Demographics, baseline in vitro fertilization (IVF) characteristics, and pregnancy outcomes, especially perinatal outcomes after FET were compared among the groups. Results: There were 137 patients in subgroup 1, 40 in subgroup 2, and 29 in subgroup 3. There were no differences in the baseline characteristics of the three groups. IVF-related data and FET-related data, such as endometrial thickness and ET no. Of embryoes, were similar among the three subgroups. The three subgroups showed no significant differences in implantation rate, biochemical pregnancy rate, abortion rate, clinical pregnancy rate or live birth rate. Besides, There was no significant difference in perinatal outcomes including very preterm delivery , preterm delivery , low birth weight , macrosomia, small for gestational age , large for gestational age , birth weight(g), birth-height(cm）and Apgar Scores. Conclusion(s): Compared with FET after their next menses, FET after two or more menstrual cycles after HSC-P does not necessarily produce superior outcomes.